Comparison of health care utilization among patients affiliated and not affiliated with healthcare professionals in China - Yafei Si; Zhongliang Zhou; Min Su; Han Hu; Zesen Yang; Xi Chen (BMC, 2020)
Abstract Background Doing "more" in healthcare can be a major threat to the delivery of high-quality health care. It is important to identify the supplier-induced demand (SID) of health care. This study aims to test SID hypothesis by comparing health care utilization among patients affiliated with healthcare professionals and their counterpart patients not affiliated with healthcare professionals. Methods We used coarsened exact matching to compare the health care utilization and expenditure between patients affiliated and not affiliated with healthcare professionals. Using cross-sectional data of the China Labour-force Dynamics Survey (CLDS) in 2014, we identified 806 patients affiliated with healthcare professionals and 22,788 patients not affiliated with healthcare professionals. The main outcomes were outpatient proportion and expenditure as well as inpatient proportion and expenditure. Results The matched outpatient proportion of patients not affiliated with healthcare professionals was 0.6% higher (P = 0.754) than that of their counterparts, and the matched inpatient proportion was 1.1% lower (P = 0.167). Patients not affiliated with healthcare professionals paid significantly more (680 CNY or 111 USD, P < 0.001) than their counterparts did per outpatient visit (1126 CNY [95% CI 885-1368] vs. 446 CNY [95% CI 248-643]), while patients not affiliated with healthcare professionals paid insignificantly less (2061 CNY or 336 USD, P = 0.751) than their counterparts did per inpatient visit (15583 CNY [95% CI 12052-19115] vs. 17645 CNY [95% CI 4884-30406]). Conclusion Our results lend support to the SID hypothesis and highlight the need for policies to address the large outpatient care expenses among patients not affiliated with healthcare professionals. Our study also suggests that as the public becomes more informed, the demand of health care may persist while heath care expenditure per outpatient visit may decline sharply due to the weakened SID. To address misbehaviors and contain health care costs, it is important to realign provider incentives.